EFEKTIVITAS PELATIHAN GURU TERHADAP PENINGKATAN KOMPETENSI MENGAJAR: STUDI LITERATUR - Aprilia Putri Nirmalasari; Barokah Isdaryanti; Joko Sutarto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the effectiveness of teacher training on improving teaching competency through a Systematic Literature Review (SLR) approach. Teacher training is an important strategy in educational human resource management to improve professionalism and the quality of learning. The development of educational technology and changes in the learning system require teachers to continuously improve their competency through various relevant and sustainable training programs. The research method used is a Systematic Literature Review by reviewing articles from national journals indexed by SINTA for the period 2021–2026. The data collection process was carried out through the Google Scholar, Garuda Kemdikbud, and SINTA databases using keywords related to teacher training and teaching competency. The selected articles were adjusted to the inclusion criteria and analyzed descriptively to obtain findings relevant to the research objectives. The results showed that teacher training has a positive influence on improving teachers' pedagogical and professional competencies. Training conducted through workshops, In-House Training (IHT), blended learning, and digital platforms such as the Merdeka Mengajar Platform has been proven to improve teachers' abilities in the use of learning technology, classroom management, the application of innovative learning methods, and curriculum understanding. Furthermore, training effectiveness is influenced by the quality of the training materials, implementation methods, instructor competence, participant motivation, and post-training follow-up. Based on the results of this study, it can be concluded that teacher training is an effective strategy for improving teaching competence and teacher professionalism. Therefore, training programs must be implemented systematically, sustainably, and tailored to teacher needs to optimally support improvements in educational quality.